Status Epilepticus: Definition, Classification, Pathophysiology, and Epidemiology - Johnson, Emily L.; Kaplan, Peter W. (Seminars in Neurology, 2020)
Status epilepticus (SE) is the state of continuous or repetitive seizures, which can occur with or without convulsions. Evolving definitions of SE take into account the concept that neuronal injury may occur at different times in different types of SE.SE that does not respond to initial treatment may become refractory or even super-refractory. Nonconvulsive SE is increasingly recognized in comatose patients in critical care units, with the growing use of continuous electroencephalogram monitoring. SE is a neurologic emergency that carries a high risk of mortality and morbidity.
Keywords: status epilepticus; nonconvulsive status epilepticus; seizures